Collaborative Participatory Accounting and Internal Audit in Increasing Public Trust in Village-Owned Enterprises - Meikhati, Ety; Sundari, Sundari; Oktaviani, Intan (LPPM Universitas Duta Bangsa Surakarta, 2025)
Village-Owned Enterprises (BUMDes) face various governance challenges, weak internal audit mechanisms, limited community participation, to inadequate human resource capacity, all of which ultimately lead to a deficit of public trust in the management of village funds. The absence of clear financial reports, delays in information disclosure, and minimal community involvement have further fueled public suspicion, while weak internal auditing has allowed potential errors, inefficiencies, and even fraud to go undetected. To overcome these issues, a transformation in financial governance is required through the implementation of participatory accounting, which directly involves the community in financial recording, reporting, and evaluation. The collaboration between these two mechanisms will create a balanced synergy between openness and oversight, thereby encouraging the establishment of transparent, accountable, and sustainable BUMDes governance. This solution must be supported by enhancing the capacity of BUMDes managers through training, adopting digital systems to simplify financial reporting, and involving village community forums as platforms for public accountability. For effective implementation, village governments are advised to issue regulations mandating participatory accounting and internal audit practices, establish independent supervisory bodies that include community representatives, and gradually adopt simple and user-friendly digital financial technologies. Furthermore, BUMDes must cultivate an organizational culture grounded in openness, integrity, and collective responsibility so that transparency is not merely a formal procedure, but a value embedded in every aspect of village enterprise management.